Intellectual capital and corporate entrepreneurship toward firm performance: a preliminary study / Ahmad Rusydan Ab Kadir ... [et al.] - Ab Kadir, Ahmad Rusydan; Ngah, Rohana; Salleh, Zarina; Sulaiman, Joehary (UiTM Cawangan Johor, 2019)
Studies have been carried out on intellectual capital but the role of corporate entrepreneurship in explaining the relationship between intellectual capital and firm performance is still scarce especially in SMEs perspective. This preliminary study investigates the relationship of intellectual capital, corporate entrepreneurship and firm performance of SMEs in Malaysian tourism industry. The preliminary study involved 68 SMEs in tourism industry. The results showed a positive significant effect between intellectual capital and firm performance. Corporate entrepreneurship played a strong role as a mediator between intellectual capital and firm performance. The findings contribute to the body of knowledge and SMEs in tourism would further benefits if intellectual capital is properly addressed. Recommendation and suggestion are provided.